SARS-CoV-2 and Pre-existing Vascular Diseases: Guilt by Association?. Issue 15 (May 2021) - Voulalas, Grigorios; Tsui, Janice; Candilio, Luciano; Baker, Daryll
Severe Acute Respiratory Syndrome coronavirus-2 has rapidly spread and emerged as a pandemic. Although evidence on its pathophysiology is growing, there are still issues that should be taken into consideration, including its effects on pre-existing peripheral vascular disease. The aim of this review is to describe the thrombotic and endothelial dysfunctions caused by SARS-CoV-2, assess if cardiovascular comorbidities render an individual susceptible to the infection and determine the course of pre-existing vascular diseases in infected individuals. A search through MEDLINE, PubMed and EMBASE was conducted and more than 260 articles were identified and 97 of them were reviewed; the rest were excluded because they were not related to the aim of this study. Hypertension, cardiovascular disease, diabetes mellitus and cerebrovascular diseases comprised 24.30% ± 16.23%, 13.29% ± 12.88%, 14.82% ± 7.57% and 10.82% ± 11.64% of the cohorts reviewed, respectively. Arterial and venous thrombotic complications rocketed up to 31% in severely infected individuals in some studies. We suggest that hypertension, cardiovascular diseases, diabetes and cerebrovascular diseases may render an individual susceptible to severe COVID-19 infection. Pre-existing vascular diseases are expected to deteriorate with SARS-CoV-2 infection as a consequence of its increased thrombotic burden and the development of endothelial dysfunction. COVID-19 has emerged only a few months ago and it is premature to predict the long-term effects to the vascular system. Its disturbances of the coagulation mechanisms and effects on vascular endothelium will likely provoke a surge of vascular complications in the coming months.